PENGARUH PEMBERIAN BERBAGAI KONSENTRASI FILTRAT DAUN BINTARO (Cerbera manghas) TERHADAP AKTIVITAS GERAK BELALANG KEMBARA (Locusta migratoria) SEBAGAI LKS MATERI PENGENDALIAN HAMA DAN PENYAKIT DI SMK - Febriana Kurniadisari; Yuni Gayatri; Abdul Ghoni (Pedago Biologi : Jurnal Pendidikan dan Pembelajaran Biologi, 2017)
Kembara Locusts (migratory locust) is corn and rice pests that attack the leaves inhibits the photosynthesis process. Bintaro Leaf (Cerbera manghas) is known to have potential as an insecticide plant because it has flavonoids, saponin, and tannins. This research is therefore aimed to find out (1) the effect of various filtrate concentrations on Bintaro leaf (Cerbera manghas) against the Kembara locusts movement activities wanderer (Locusta migratoria); (2) the form of teaching materials that can be made from the results of this research. This research was experimental research using Randomized Posttest Only design with 4 treatments and 6 repetitions. The concentration used was 25%, 50% and 75%. The independent variables this research was different filtrate concentrations of Bintaro leaf (Cerbera manghas) while the dependent variable is the movement activities of Kembara locusts (Locusta migratoria). Based on the result of Anova analysis, it is found that there is an effect of the filtrate concentration of Bintaro leaf (Cerbera manghas) on the movement activities of Kembara locusts (Locusta migratoria). While the most effective concentration as an insecticide found is a concentration of 50%, this is because low concentrations can give a significant effect to the movement activities. Lastly, these findings can be utilized as teaching material on the topic of pest and disease control at Vocational High Schools.